The generation of a liquid jet induced by a pressure impulse (Experimental study on the jet velocity) - Akihito KIYAMA; Yuto NOGUCHI; Yoshiyuki TAGAWA (Nihon Kikai Gakkai ronbunshu, 2014)
A liquid jet is important in various mechanical systems such as medical applications. Recently, a method for generating a thin jet by a laser-induced shock wave is proposed in a previous research. In this paper, we adopt another method for generating a thin jet as a possible alternative method. In order to investigate similarity between both jets generated by each method, we compare the velocity of the jet in our systematic experiments with a semiempirical relation reported by the previous research. We drop a liquid-filled test tube with a rounded bottom on the floor, leading to the emergence of a thin liquid jet into the air. The experimental parameters are the depth of a liquid, the diameter of the test tube, and the impact velocity. Within certain experimental conditions, our experimental results agree well with the semiempirical relation. It suggests that the jet generated by our method has similarity to the jet in the previous research. In other conditions, however, we find a remarkable fact that the jet can be faster than the value predicted by the semiempirical relation. In this case, we observe cavitation bubbles inside a liquid. We further investigate a relation between a liquid jet and the cavitation number using a high-speed camera. We introduce the cavitation number as a criterion for describing the condition of the cavitation occurrence. The criterion is confirmed by additional experiments. We also find a strong relation between the maximum volume of cavitation bubbles and the jet velocity.